Pengaruh Ekstrak Kasar Daun Keji Beling (Strobilanthes crispus) terhadap Infeksi Bakteri Aeromonas hydrophila Secara In Vitro - Genesia Gerrine; Arief Prajitno; Mohamad Fadjar; Rahmalia Eka Kenitasari (Jurnal Penelitian Pendidikan IPA, 2023)
Keji beling leaves (Strobilanthes crispus) can be the solution to cure the fish that infected by Aeromonas hydrophila because it contained active compounds. The purpose of this study was to determine the active compounds contained in the crude extract of keji beling leaves (S. crispus) and their ability to inhibit the growth of A. hydrophila. The tests which are used in this study were phytochemical test, MIC test, disk diffusion test, and SEM test. Phytochemicals analysis showed the presence of active compounds are flavonoid, alkaloid, tanin, and triterpenoid. The result of MIC test showed that concentration of 100 mg/l with a value of 0.389 was the lowest absorbance of the keji beling (S. crispus) crude leaves extract. The inhibition test used disk diffusin test with five concentrations of keji beling (S. crispus) crude leaves extract with three replications: 50 mg/l, 100 mg/l, 150 mg/l, 200 mg/l, and 250 mg/l, with the observation time of 24 hours post-incubation and 48 hours post-incubation. The concentration of 250 mg/l had the highest inhibition zone. The result of SEM analysis showed that keji beling (S. crispus) crude leaves extract can damage the cell walls of A. hydrophila and lysis the bacterial cells.